2009
DOI: 10.4021/jocmr2009.10.1267
|View full text |Cite
|
Sign up to set email alerts
|

The Unstimulated Salivary Flow Rate in a Jordanian Healthy Adult Population

Abstract: BackgroundEarly diagnosis of xerostomia is very important for oral health. The purpose of this study was to determine the unstimulated whole salivary flow rates (UWSFR) in a Jordanian Arab population aged 15 years and older. The effect of age, gender, height, weight, body mass index (BMI), smoking, alcohol consumption, and dental conditions, on UWSFR was also investigated.MethodsThe study was conducted on 244 subjects, 110 males and 134 females, with an average age of 33 ± 15.5 years. They were healthy, unmedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 29 publications
6
18
0
4
Order By: Relevance
“…Nagler 20 reported that SFR values in smokers were higher compared with nonsmokers, while in some studies SFRs were found to be similar in both populations. 21,22 Rad et al 23 reported significantly lower SFRs and a significantly higher frequency of xerostomia symptoms in smokers compared with nonsmokers, in accordance with previous studies. 9,24 There are numerous factors found to influence salivary flow, including age, sex, health status, or medication used, that could induce the inconsistency in the obtained data.…”
Section: Discussionsupporting
confidence: 91%
“…Nagler 20 reported that SFR values in smokers were higher compared with nonsmokers, while in some studies SFRs were found to be similar in both populations. 21,22 Rad et al 23 reported significantly lower SFRs and a significantly higher frequency of xerostomia symptoms in smokers compared with nonsmokers, in accordance with previous studies. 9,24 There are numerous factors found to influence salivary flow, including age, sex, health status, or medication used, that could induce the inconsistency in the obtained data.…”
Section: Discussionsupporting
confidence: 91%
“…Potentially relevant studies that examined salivary flow rate in adults of different ages were identified through lit- 15,16,20,22,23,25,27,29,31,34,35,39,41,52,57,61 Cotton rolls or Saxon Test 18,44,45,54,58,59 erature searches of the PubMed, EBSCOhost, Web of Science, Cochrane, EMBASE, Dissertations and Theses, and Scopus databases, published from the inception of the databases through June 2013. Although search terms varied slightly across databases, the terms "saliva" and "salivation" or "secretion" and "aged" or "aging" and "normal" or "disease-free" were used as Medical Subject Heading terms, key words, or subject headings (Online Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…An association between salivary flow and the number of teeth present in the mouth has been documented in other studies. Sawair et al (23) conducted a study among adults in Jordan and found that the greater the number of missing teeth, the lower the salivary flow. In a study conducted in Japan (17), they observed that a greater number of teeth in the mouth was directly associated with salivary flow.…”
Section: Islas-granillo Et Almentioning
confidence: 99%